Penggunaan virgin coconut oil (vco) sebagai desinfektan dalam penyimpanan telur ayam ras - Anastasia A. Todja; Annytha I. R. Detha; Diana A. Wuri (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
Eggs from commercial laying chicken are comestibles from animal source that are easy to deteriorate and rot in room temperature. Consequently, a method to improve eggs’ storage life is needed. Preserving eggs using Virgin Coconut Oil (VCO) may be taken into consideration. This research aimed to identify the effects of VCO usage as antibacteria on storage life and quality of eggs of commercial laying chicken in Kupang district. Samples used were 63 eggs of commercial laying chicken aged 0 day from Candra Farm in Oesusu, East Kupang, Kupang District. Experiment design used was a completely randomized design with three repetitions. Preservation method, comprising 3 treatments which are non-VCO (T0), with VCO by smearing (T1) and by spraying (T2), in seven times observation, which were held on 10th day (P1), 15th day (P2), 20th day (P3), 25th day (P4), 30th day (P5), 35th day (P6) and 40th day (P7). Quality assessment of the eggs were organoleptic quality, physical quality comprising yolk index, albumen index, air sac depth, egg pH and microbiological quality determined from Total Plate Count (TPC). The results showed that VCO usage has a significant effect (P<0,05) on storage life and egg quality during the 40 day storage. Eggs treated with VCO has better storage life and better quality compared to those without VCO when saved in room temperature (28-32 oC). The Least Significant Difference test showed that there is no significant difference between eggs treatment with VCO by smearing and spraying (P>0.05). this means that both of the methods can be used to improve storage life and quality of the eggs. It can be concluded that eggs that are not treated with VCO are well consumed within 10 days, while eggs treated with VCO and stored in room temperature are safe to be consumed within 20 days